Influências exôgenas na qualidade bacteriológica da água, solo e camarão (Litopenaeus vannamei), em quatro fazendas de camarão do Estado do Ceará - Carvalho, Fátima Cristiane Teles de (2006)
The objective of the present study was to evaluate the influence of the environment upon marine shrimp farming with regard to bacteriological quality of the water, pond sediments and livestock (Litopenaeus vannamei). The study was carried out on four shrimp farms in Ceará (1, 2, 3 and 4). Of the eight samplings performed, 3 involved water (one outside the farm-PEX, one at the pumping site-PB, and one in the pond-PV); 3 involved sediment (at locations PEX, PB and PV), and two consisted of harvested and processed shrimp. Samplings Were carried out in different seasons (dry, intermediary and rainy) and totaled 288 individual samples (108 water; 108 sediment; 72 shrimp). The most probable numbers (MPN) of total coliforms (TC), fecal coliforms (FC) and Escherichia coli were determined and samples were investigated for Salmonella strains. The bacteriological contamination observed on the shrimp farms was predominantly caused by TC and FC and was most intense during the intermediary season. Farms 2 and 4 yielded the highest concentrations of FC in water and sediment, respectively, at sampling locations PEX and PB during the three seasons. No shrimp sample presented E. coli values above those permitted by the European Commission (EU). However, on account of the Salmonella values observed, Farms 2 and 4 would be barred from exporting shrimp to the EU. In addition, water sampled at Farm 3 contained Salmonella strains capable of infecting the livestock. Only Farm 1 presented an exogenous and endogenous environment free of fecal contamination. The presence of Salmonella and E. coli in water and shrimp samples is disquieting, considering the fact that theses pathogens are of fecal origin and that their natural habitat is the intestinal tract of warm-blooded animals.